"Another Tyrtaeus": Byron and the Rhetoric of Philhellenism. Issue 1 (1st April 2021) - Davis, William
Abstract : This essay investigates the philhellenist strategy of labelling Byron "another Tyrtaeus" in support of the Greek uprising against the Ottoman Empire that began in 1821. Beginning with a political speech delivered in Louisiana in 1824, I examine several examples of Byron-as-Tyrtaeus, including poems in both German and French. I argue that depicting Byron as the avatar of the Spartan poet functions to support the notion that modern Greeks are directly connected to their glorious past and therefore deserving of Western aid. If Byron is another Tyrtaeus, it follows that modern Greece is another Hellas. This use of "Byron" likewise insists that "we are all Greeks, " positioning modern Greeks as white, European, and Christian as opposed to their Ottoman oppressors who are othered as barbarians. I note the irony and hypocrisy of philhellenes from a slave-holding nation calling on their fellows to free Greece from Turkish enslavement.